Increasing strength of a biomedical Ti-Nb-Ta-Zr alloy by alloying with Fe, Si and O. (July 2017) - Stráský, Josef; Harcuba, Petr; Václavová, Kristína; Horváth, Klaudia; Landa, Michal; Srba, Ondřej; Janeček, Miloš
Abstract: Low-modulus biomedical beta titanium alloys often suffer from low strength which limits their use as load-bearing orthopaedic implants. In this study, twelve different Ti-Nb-Zr-Ta based alloys alloyed with Fe, Si and O additions were prepared by arc melting and hot forging. The lowest elastic modulus (65 GPa) was achieved in the benchmark TNTZ alloy consisting only of pure β phase with low stability due to the 'proximity' to the β to α'' martensitic transformation. Alloying by Fe and O significantly increased elastic modulus, which correlates with the electrons per atom ratio (e/a). Sufficient amount of Fe/O leads to increased yield stress, increased elongation to fracture and also to work hardening during deformation. A 20% increase in strength and a 20% decrease in the elastic modulus when compared to the common Ti-6Al-4V alloy was achieved in TNTZ-Fe-Si-O alloys, which proved to be suitable for biomedical use due to their favorable mechanical properties. Highlights: Ti-35.3Nb-5.7Ta-7.3Zr alloy was alloyed with Fe, Si and O to increase its strength. Elastic modulus correlates with the electrons per atom ratio (e/a). Sufficient amount of Fe/O enhances the yield stress and causes work hardening. TNTZ-Fe-Si-O alloys have lower modulus and higher strength than Ti6Al4V alloy.